1637 : the French correction - Flint, Eric; Hunt, Walter H. (Ring of fire (Riverdale, N.Y.) ;, 2025)
"Tensions build in France following the ascension of Gaston to the throne of his murdered brother, but there are factions supporting the claim of King Louis' surviving infant son. As France moves toward civil war, other parties, both visible and invisible, maneuver to take advantage of the increased tension. Who will survive to reign over France--King Gaston, the exiled child and his regents, or the King of Spain?"--